Strengthening Popular Participation in the African Union : a Guide to AU Structures and Processes. - Chitiga, Rudo.; Manby, Bronwen; AfriMAP; Open Society Foundation; Open Society Foundations; Open Society Institute; Open Society Initiative for Southern Africa (OSISA); Oxfam (Open Society Institute Network, 2010)
The African Union (AU) has committed to a vision of Africa that is 'integrated, prosperous and peaceful - driven by its own citizens, a dynamic force in the global arena' (Vision and Mission of the African Union, May 2004). This guide is an effort to take up the challenge of achieving this vision. It is a tool to assist activists to engage with AU policies and programmes. It describes the AU decision-making process and outlines the roles and responsibilities of the AU institutions. It also contains a sampling of the experiences of those non-governmental organisations (NGOs) that have interacted with the AU.
Introduction : the purpose of this guide -- AU organs & institutions -- Influencing AU decisions & policies -- The union government debate -- Appendix 1. AU regions -- Appendix 2. Regional economic communities recognised by the African Union -- Appendix 3. Useful websites and contacts.
This report is also published in French in PDF format.
Keywords: African Union; African Union; Non-governmental organizations -- Africa; Non-governmental organizations; Politics and government; Africa -- Politics and government; Africa